PENGARUH PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PABRIK KELAPA SAWIT 1 BUKIT PAYUNG KABUPATEN KUNTAN SINGINGI - Fahrial Fahrial; Andri Romanto (UIR Press, 2018)
This study aimed to determine the effect of staffing on the performance of employees at mills I Bukit Kuantan District Singingi Umbrella all employees mills I Mount Umbrella, sampling technique using simple random sampling as many as 57 people. In analyzing the data of this study data analysis using descriptive and quantitative methods, namely by processing the data obtained from the company, then analyzed using the theoretical basis as a means to solve problems, and then make a conclusion. The research result is seen from the results of the t-test where the value t count>t table (32,639>2,004) there is a significant positive influence between the placement of employees on employee performance. Judging from the coefficient of determination R Square of 0,951. This shows that the percentage contribution of staffing influence on employee performance is at 95%. While the remaining 5% is influenced by other variables not included in the study.